SOCIAL SECURITY FOR PERSONS WITH DISABILITIES IN SOUTH AFRICA: COMPLIANCE WITH ARTICLE 28(2) OF THE CONVENTION ON THE RIGHTS OF PERSONS WITH DISABILITIES - Basson, Yvette (Obiter, 2024)
The United Nations Convention on the Rights of Persons With Disabilities (CRPD) was adopted in 2006 in order to address continued marginalisation of persons with disabilities. Since the adoption of the CRPD, the rights of persons with disabilities have received more scrutiny than previously. The Preamble to the CRPD states that “persons with disabilities continue to face barriers in their participation as equal members of society and violations of their human rights in all parts of the world”. The founding principle of the CRPD is that persons with disabilities are entitled to participate fully and equally in society, irrespective of their individual disability. To achieve this goal, the CRPD provides for a number of rights that must be implemented by States Parties that have signed and ratified it. The rights included in the CRPD contribute towards the achievement of full and equal participation in society. Article 28 of the CRPD guarantees two rights that contribute towards the achievement of full and equal participation in society of persons with disabilities. These are the right to an adequate standard of living, and the right to social protection. This article establishes the scope and content of the right to social security as a component of the rights guaranteed in article 28. To this end, the obligations created by the CRPD related to social security provided by States Parties are established. The current South African social security system pertaining to persons with disabilities is discussed and analysed to determine whether it is compliant with the obligations created in article 28 of the CRPD. Finally, shortcomings in the existing social security system are identified and potential remedies suggested to address these.